Russia scrambles as EU surges in Caucasus - Bhadrakumar, M. K. (Indian Punchline, 2023)
Armenian PM Nikol Pashinyan (above) is turning to the West  Armenia no longer disputes that Nagorno-Karabakh is part of Azerbaijan. The prospect of peaceful resolution of a regional conflict ought to be good news, but this is an incredibly complex situation with an external environment where a brutal war is raging with no end in sight, … Continue reading "Russia scrambles as EU surges in Caucasus"
Keywords: armenia; backgrounder; caucasus